Audience Reception Analysis of Muslim Viewers Toward Islamophobia in the Film Extraction - Suthon Muhammad Putra Mahardhika; Ela Rosalinda; Erik Andri Aliyanto; Anisa Yuliana Putri (Syiar: Jurnal Komunikasi dan Penyiaran Islam, 2026)
The film Extraction (2020) is considered to negatively represent Bangladesh and stereotype Muslims, reinforcing Islamophobia through characterization, setting, and religious symbols, thereby influencing public perception. This study aims to analyze how Muslim audiences receive, interpret, and respond to the construction of Islamophobia in the film Extraction. A qualitative approach was employed, using audience reception analysis and Stuart Hall’s Encoding/Decoding theory, with data collected through interviews with Muslim informants who watched the film. The results reveal diverse receptions among Muslim audiences. A dominant-hegemonic position emerges among viewers who accept the film’s representation as a social critique or a criminal reality. The negotiated position is found in audiences who enjoy the film’s action but reject the generalization of Muslim stereotypes. The oppositional position is strongest among audiences with high religious knowledge and cultural context, who reject the narrative stigmatizing Muslims and associating them with terrorism. Audience interpretation processes are influenced by cultural background, personal experience, and religious knowledge, making acceptance of Islamophobia in the film selective and active. Muslim audiences actively interpret the film, resist negative stereotypes, and respond based on cultural, religious, and personal contexts. This study enriches the literature on audience reception and Islamophobia studies, and encourages the media to be more inclusive and critical of Muslim stereotypes.